ENDOSCOPIC EXAMINATION OF UPPER GASTROINTESTINAL TRACT - Dr. Ahmed Mohammed Ahmed; Abdullah Abdulkhaliq Qazzaz; Dr. Hydair Sachet Khalaf (Scholar Express Journals, 2022)
It is well-known that most of the descriptions of the gastrointestinal tract (specifically upper gastrointestinal tract concerned in our study), were obtained from anatomical observation of a cadaver and few clinical notes. Consequently, the clinicians depend on these points in their diagnosis and managements.
Keywords: informations; clinicians; points; observation